Nesfatin-130−59 Injected Intracerebroventricularly Differentially Affects Food Intake Microstructure in Rats Under Normal Weight and Diet-Induced Obese Conditions - Prinz, Philip; Teuffel, Pauline; Lembke, Vanessa; Kobelt, Peter; Goebel-Stengel, Miriam; Hofmann, Tobias; Rose, Matthias; Klapp, Burghard F.; Stengel, Andreas (Frontiers in Neuroscience, 2015)
Nesfatin-1 is well established to induce an anorexigenic effect. Recently, nesfatin-1(30-59), was identified as active core of full length nesfatin-1(1-82) in mice, while its role in rats remains unclear. Therefore, we investigated the effects of nesfatin-1(30-59) injected intracerebroventricularly (icv) on the food intake microstructure in rats. To assess whether the effect was also mediated peripherally we injected nesfatin-1(30-59) intraperitoneally (ip). Since obesity affects the signaling of various food intake-regulatory peptides we investigated the effects of nesfatin-1(30-59) under conditions of diet-induced obesity (DIO). Male Sprague-Dawley rats fed ad libitum with standard diet were icv cannulated and injected with vehicle (5µl ddH2O) or nesfatin-1(30-59) at 0.37, 1.1 and 3.3 µg (0.1, 0.3, 0.9 nmol/rat) and the food intake microstructure assessed using a food intake monitoring system. Next, naïve rats were injected ip with vehicle (300 µl saline) or nesfatin-1(30-59) (8.1, 24.3, 72.9 nmol/kg). Lastly, rats were fed a high fat diet for 10 weeks and those developing DIO were icv cannulated. Nesfatin-1 (0.9 nmol/rat) or vehicle (5µl ddH2O) was injected icv and the food intake microstructure assessed. In rats fed standard diet, nesfatin-1(30-59) caused a dose-dependent reduction of dark phase food intake reaching significance at 0.9 nmol/rat in the period of 4-8 h post injection (-29%) with the strongest reduction during the 5th h (-75%), an effect detectable for 24 h (-12%, p<0.05 vs. vehicle). The anorexigenic effect of nesfatin-130-59 was due to a reduction in meal size (-44%, p<0.05), while meal frequency was not altered compared to vehicle. In contrast to icv injection, nesfatin-1(30-59) injected ip in up to 30-fold higher doses did not alter food intake. In DIO rats fed high fat diet, nesfatin-1(30-59) injected icv reduced food intake in the 3rd h post injection (-71%), an effect due to a reduced meal frequency (-27%, p<0.05), while meal size was not altered. Taken together, nesfatin-1(30-59) is the active core of nesfatin-1(1-82) and acts centrally to reduce food intake in rats. The anorexigenic effect depends on the metabolic condition with increased satiation (reduction in meal size) under normal weight conditions, while in DIO rats satiety (reduction in meal frequency) is induced.